2013
DOI: 10.1099/mic.0.067637-0
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a model for Vibrio parahaemolyticus virulence

Abstract: Vibrio parahaemolyticus is a Gram-negative, naturally occurring marine bacterium. Subpopulations of strains belonging to this species cause an acute self-limiting gastroenteritis in humans and, less commonly, wound infections. In vivo models to differentiate avirulent and virulent strains and evaluate the pathogenic potential of strains of this species have been largely focused on the presence of known virulence factors such as the thermostable direct haemolysin (TDH), the TDH-related haemolysin (TRH) or the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…According to the results of Paranjpye et al. (), it was confirmed that the Vp13 strain also was pathogenic to zebrafish larvae. Due to the existence of mucosal and cutaneous immune, bacteria are uneasy to infect healthy zebrafish larvae.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…According to the results of Paranjpye et al. (), it was confirmed that the Vp13 strain also was pathogenic to zebrafish larvae. Due to the existence of mucosal and cutaneous immune, bacteria are uneasy to infect healthy zebrafish larvae.…”
Section: Discussionmentioning
confidence: 84%
“…From our results, the Vp 13 strain contained tdh + , tlh + , trh À genotype characteristic, and its LD 50 to zebrafish larvae was 3.63 9 10 7 CFU/ml. According to the results of Paranjpye et al (2013), it was confirmed that the Vp13 strain also was pathogenic to zebrafish larvae. Due to the existence of mucosal and cutaneous immune, bacteria are uneasy to infect healthy zebrafish larvae.…”
Section: Discussionmentioning
confidence: 91%
“…También, Reyes-Velazquez et al, (2010) mencionan que las concentraciones observadas de V. parahaemolyticus en C. virginica pueden también ser producidas por la variación estacional de la población por "hibernación" en el sedimento o en conjunto con la fauna marina, seguidos por el crecimiento poblacional y escorrentías de altas concentraciones de materia orgánica y nutrientes a las lagunas como Mandinga, Veracruz. Paranjpye et al, (2013) …”
Section: Discussionunclassified
“…All three of these organisms have been modeled in the zebrafish (He et al, 2011; Pan et al, 2011; Paranjpye et al, 2013; Wang et al, 2008). …”
Section: Aquatic Bacterial Pathogens Modeled In the Zebrafishmentioning
confidence: 99%